2009
DOI: 10.1371/journal.pone.0005314
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Coping Style Increases the Power of Gene Expression Studies

Abstract: BackgroundIndividuals of many vertebrate species show different stress coping styles and these have a striking influence on how gene expression shifts in response to a variety of challenges.Principal FindingsThis is clearly illustrated by a study in which common carp displaying behavioural predictors of different coping styles (characterised by a proactive, adrenaline-based or a reactive, cortisol-based response) were subjected to inflammatory challenge and specific gene transcripts measured in individual brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 28 publications
5
102
0
1
Order By: Relevance
“…The results from this study show that coping style is playing an important role in explaining differences in RMR and that the interpretation of results should take the individual's coping style in consideration. Recently, the incorporation of an individual's coping style for the interpretation of data that typically only considers average values revealed a significant influence of coping styles on the interpretation of data (MacKenzie et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from this study show that coping style is playing an important role in explaining differences in RMR and that the interpretation of results should take the individual's coping style in consideration. Recently, the incorporation of an individual's coping style for the interpretation of data that typically only considers average values revealed a significant influence of coping styles on the interpretation of data (MacKenzie et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al, 2010). In either case, the results suggest that active copers, as opposed to passive copers can be behaviourally characterised by (1) actively trying to escape from a stressor (Silva et al, 2010), (2) showing higher feed motivation after transfer to a new environment (Øverli et al, 2007), (3) being more risk taking and exploratory when exposed to novelty (Øverli et al, 2006;Frost et al, 2007;MacKenzie et al, 2009) and (4) being more aggressive (dominant) during aggressive encounters (Øverli et al, 2004). In addition, active copers exhibit typical neuroendocrine responses such as (1) lower hypothalamus-pituitary-interrenal (HPI) activity (Silva et al, 2010), (2) lower HPI reactivity (Øverli et al, 2005), (3) higher sympathethic reactivity and lower parasympathetic reactivity (measured as opercular beat rate, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other commonly used definitions, such as personalities (Gosling 2001), boldness or behavioural syndrome (Sih et al 2004), refer to the same phenomenon but typically in the context of individual consistency in behaviour. Considering coping styles as continua of behavioural responses to external stressors, several behavioural axes have been recognized, among which the exploratory behaviour along a proactive-reactive continuum (Coleman & Wilson 1998, Reale et al 2007, MacKenzie et al 2009, Raoult et al 2012. Variation along this continuum can affect survival and reproductive success (Carere et al 2003, Carere & van Oers 2004 and has been studied in a variety of fish species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Variation along this continuum can affect survival and reproductive success (Carere et al 2003, Carere & van Oers 2004 and has been studied in a variety of fish species (e.g. Huntingford 1976, Coleman & Wilson 1998, Schjolden et al 2005, MacKenzie et al 2009, Huntingford et al 2010, Pavlidis et al 2011, Raoult et al 2012. MacKenzie et al (2009) showed that proactive and reactive common carp (Cyprinus carpio) responded oppositely to inflammatory challenge regarding 80% of investigated immune-related gene transcripts.…”
Section: Introductionmentioning
confidence: 99%